2015
DOI: 10.1089/scd.2014.0235
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Growth of Tissues Derived from Cranial Neural Crest and Primitive Mesoderm Is Dependent on the Ligation Status of Retinoic Acid Receptor γ: Evidence That Retinoic Acid Receptor γ Functions to Maintain Stem/Progenitor Cells in the Absence of Retinoic Acid

Abstract: Retinoic acid (RA) signaling is important to normal development. However, the function of the different RA receptors (RARs)--RARα, RARβ, and RARγ--is as yet unclear. We have used wild-type and transgenic zebrafish to examine the role of RARγ. Treatment of zebrafish embryos with an RARγ-specific agonist reduced somite formation and axial length, which was associated with a loss of hoxb13a expression and less-clear alterations in hoxc11a or myoD expression. Treatment with the RARγ agonist also disrupted formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…RA and FGF signaling pathways also function together to pattern the posterior portion of embryos and control NC migration (Martinez-Morales et al, 2011). For example, knockdown of the RA receptor-Υ causes defects in NC progenitor cells in zebrafish embryos in addition to aberrant paraxial mesoderm development (Wai et al, 2015). There are contrasting studies with regards to RA in NC development.…”
Section: Retinoic Acidmentioning
confidence: 99%
“…RA and FGF signaling pathways also function together to pattern the posterior portion of embryos and control NC migration (Martinez-Morales et al, 2011). For example, knockdown of the RA receptor-Υ causes defects in NC progenitor cells in zebrafish embryos in addition to aberrant paraxial mesoderm development (Wai et al, 2015). There are contrasting studies with regards to RA in NC development.…”
Section: Retinoic Acidmentioning
confidence: 99%
“…Treatment of zebrafish embryos with a RARγ-specific agonist adversely affected the development and growth of tissues that form from neural crest and lateral plate mesodermal stem and progenitor cells that express RARγ. These studies revealed that RARγ, which can play a role in cell reprogramming, has to be inactive at the stem/progenitor stage of development for these cells to make an appropriate decision to differentiate along a pathway [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from studies of zebrafish development further support the view that RARγ activity is important for the maintenance of stem/progenitor cell populations [ 57 ]. In zebrafish, there are two major RAR isotypes, RARα and RARγ, and treatment of zebrafish embryos four hours post-fertilization with the RARγ-selective agonist AGN205327 blocked the development and growth of tissues that are derived from cranial neural crest and primitive mesoderm.…”
Section: Rarγ Is a Fundamental Control On Stem Cell Behaviormentioning
confidence: 72%